Análise de intervenções urbanas e suas articulações com a legislação na cidade de Belo Horizonte - Priscila de Oliveira Tavares (2013)
This study proposes to analyze urban interventions accomplished in the city of Belo Horizonte. They were selected according to their degree of importance as responsible for the changes in the structural and fuctional aspect of the city as well as generator of other urban centers. Historical and circumstantial facts that influenced in the planning and conception of the new capital of Minas, its unequal growth crossing the predicted boundaries and the creation of laws and codes as a way to order and regulate the urban functions were reseached. Through the comparison ofurban projects, that caused impact in Belo Horizonte, with programs implemented in other Brazilian cities and in other countries cities, it was possible to identify the efficiency on the application of some measures, as well as aspects here considered problematic of some specific proposals. Strategies to guarantee improvement and effective development of the cities, such as the adopting of new routines for restored buildings, the revitalization or under-utilisation of degraded areas and the integration of functions were also studied. It was analysed implemented initiatives in search of solutions for the most frequent demands, such as the adjustment of the city to abosrb the accelerated increase of population, the elimination of obstacles that inhibits urbanaccessibility and mobility.